ANALISIS KASUS PEMERASAN AKIBAT PENYALAHGUNAAN PADA SOSIAL MEDIA - Sinta Nuriyah; Wiwik Afifah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Technology has made it easier to get the information we need, which is progress.However, the advancement of technology was also used as an opportunity for cybercrime during its development.As the emergence of cases of defamation, cases of hate speech, cases of hoax, cases of fraud pretended to be the buying and selling of online, cases of online prostitution, and the case other cybercrime, where is the moment, abuse of social media is facilitating the spread of cybercrime in the cyberspace?More than half of the bad people in 2018 came from social media, especially Facebook and Twitter.According to the findings of the study, social media abuse continues to contribute to the spread of cybercrime to this day.The majority of those who engage in cybercrime on social media, whether intentionally or unintentionally, will be subject to prosecution under the law No.11th year on electronic transactions and information (UU ITE).